EVALUASI PENYUSUNAN LAPORAN KEUANGAN ENTITAS NIRLABA PADA YAYASAN PENDIDIKAN XYZ - Aprilia, Ruth Grace; Sihombing, Salmon; Tobing, Suzanna Josephine L. (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
ABSTRACT XYZ Education Foundation is a non-profit social organization that provides services in the form of elementary school to high school. The foundation's resources come from donations that managed for its operational activities. In order for the foundation's finances to be well managed and the services provided to be sustainable, the foundation prepares the financial statements to be used by the foundation's management and donors in assessing the performance of the foundation. The financial statements of non-profit organizations are set out in SFAS 45 on reporting of nonprofit entities, but in practice the XYZ Education Foundation applies SAK ETAP for the frame of its financial statements, although its implementation SAK ETAP cannot be used in the foundation's financial statements because the foundation is generally devoted to the community, so that the foundation has public accountability. The financial statement of education foundation has similar frame with the financial reporting of PSAK 45, but not all have been implemented by the foundation. The management of the foundation is the responsible party for the preparation and presentation of the financial statements so that management needs to rethink the accounting policies that should be used in the foundation's financial statements. Keyword: yayasan, laporan keuangan, Pernyataan Standar Akuntansi Keuangan.